2015
DOI: 10.14474/ptrs.2015.4.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balance imagery of semi-tandem stance on a flat floor and balance beam for postural control: a comparison between older and younger adults

Abstract: Objective: Balance is a preceding task for functional activities in daily activities as well as community-dwelling activities. To learn skilled and functional activities, it is also necessary to imagine an appropriate and effective movement representation used to plan and execute the functional activities. The purpose of this study was to evaluate the effects of balance imagery of semi-tandem stance on a flat floor and balance beam on balance abilities for elderly and young adults. Design: Cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To apply attentional focus more effectively for clinical exercise rehabilitation, the physical development level (e.g., developmental age, skill level, task difficulty, etc.) should be considered [3,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…To apply attentional focus more effectively for clinical exercise rehabilitation, the physical development level (e.g., developmental age, skill level, task difficulty, etc.) should be considered [3,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is considered that WE programs for children with CP may be used to motivate children who lack confidence in exercising on the ground. Movement in the water is free from the risk of falling compared to the ground, and because it is free and comfortable, abnormal tone can be stabilized, which allows for the children with CP to actively participate in the exercise program and exhibit improved postural control function [13][14][15][16][17]. Ballaz et al [5] reported improvement instanding and walking ability of children with CP with low physical abilities with a Gross Motor Function Classification System score of 3 to 4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exercise programs with rhythmic motion have a greater effect on improving physical fitness than general muscle strength-aerobic exercise [21]. More than 30% of the elderly suffer from depression, which is highly correlated with falls [22], and is a factor that reduces self-esteem and quality of life [23]. With the case of depression, participation in a rhythmic exercise program has the effect of stabilizing the emotions [24], and as participation in regular exercise increases, a more positive influence on body function can be observed, which subsequently raises life satisfaction [25].…”
Section: Introductionmentioning
confidence: 99%